Creativity and innovation performance through employees’ empowerment in uae smart government - Jumma Alhosani, Jumaa Mohammed (2019)
The purpose of this study is to empirically investigate impact of transformational, transactional and laissez-faire leadership on employees’ innovation and creativity and employees’ empowerment. Over the past decades, employees have become an organiser in coordinating work within organisation. This trend creates new challenges for leaders as they are expected to innovate individual employees and to improve their creativity simultaneously. This study proposes a conceptual framework for understanding leadership styles and employees’ empowerment to individual employee which would influence innovation and creativity. The conceptual framework includes employees’ empowerment and support for innovation as mediating variables in the effect of leadership styles on employees’ innovation and creativity. The study also validates the proposed conceptual framework using a second-order confirmatory factor analysis technique, namely, structural equations modeling, with the data collected from 597 employees of four e-Government organisations in the UAE. The findings suggest that transformational, transactional and laissez-faire leadership has significant positive impact on employees’ innovation and creativity. Moreover, employees’ empowerment has partial mediation effect in the relationship between leadership styles and employees’ innovation and creativity. This study contributes to the research that identifies employees’ innovation and creativity influenced by transformational, transactional and laissez-faire leadership that can affect employee performance, particularly in the context of UAE-based e-Government organisations.